Nucleolin forms a specific complex with a fragment of the viral (minus) strand of minute virus of mice DNA. - Barrijal, S (1992)
Nucleolin, a major nucleolar protein, forms a specific complex with the genome (a single-stranded DNA molecule of minus polarity) of parvovirus MVMp in vitro. By means of South-western blotting experiments, we mapped the binding site to a 222-nucleotide motif within the non-structural transcription unit, referred to as NUBE (nucleolin-binding element). The specificity of the interaction was confirmed by competitive gel retardation assays. DNaseI and nuclease S1 probing showed that NUBE folds into a secondary structure, in agreement with a computer-assisted conformational prediction. The whole NUBE may be necessary for the interaction with nucleolin, as suggested by the failure of NUBE subfragments to bind the protein and by the nuclease footprinting experiments. The present work extends the previously reported ability of nucleolin to form a specific complex with ribosomal RNA, to a defined DNA substrate. Considering the tropism of MVMp DNA replication for host cell nucleoli, these data raise the possibility that nucleolin may contribute to the regulation of the parvoviral life-cycle.